UGANDAN-AMERICAN ECONOMIC RELATIONS: FROM INDEPENDENCE TO THE 1971 MILITARY COUP - Hawraa Razzaq Hassan; Ali Adum Mohmad (Scholars Digest Publishing, 2024)
American economic interests in South, Central, and East Africa constitute a significant but not overwhelming portion of the United States' foreign trade and investments. This region serves as a crucial supplier of strategic materials, including diamonds, cobalt, chromite, manganese, copper, and sisal, which are vital to the free world. The United States heavily depends on these resources, along with a variety of minerals and agricultural products. Consequently, the primary objectives of the United States in this region are to safeguard its economic interests and counteract communist influence.
Keywords: American economic interests in South, Central, and East Africa constitute a significant but not overwhelming portion of the United States' foreign trade and investments. This region serves as a crucial supplier of strategic materials, including diamonds, cobalt, chromite, manganese, copper, and sisal, which are vital to the free world. The United States heavily depends on these resources, along with a variety of minerals and agricultural products. Consequently, the primary objectives of the United States in this region are to safeguard its economic interests and counteract communist influence.